Trial and Error edited by F Shapiro and J Garry - Petersson, Sandra (Victoria University of Wellington Law Review, 2001)
Fred Shapiro and Jane Garry (eds) Trial and Error: An Oxford Anthology of Legal Stories (Oxford University Press, Oxford, 1998). Hardcover, 479 + xii pages, NZ50. This article is a book review of Trial and Error, an anthology of stories that encompass the law. Petersson argues that the book is primarily a book to be enjoyed, even with its scholarly qualities. She concludes that the book is an excellent starting point for any study of law in literature, whether for personal interest or as part of a formal course of study.